2021
DOI: 10.5539/elt.v14n6p84
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Learning Outcomes and Interaction Mode Matter: Students’ Experience of Taking Online EFL Courses During COVID-19

Abstract: The recent health emergency has changed the teaching mode globally, with traditional classroom teaching shifting to online platforms. This created challenges for both foreign/second language teachers and learners. Some recent studies investigated the challenges brought by online teaching from the teachers’ perspective; however, little is known about how students perceive the effectiveness of online language learning based on their experiences. Therefore, this study surveyed 252 Chinese students who t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Prelearning is the initial stage of constructing the meaning of the knowledge students have learned. Before the lesson, teachers post learning objectives and learning content online, upload multimodal learning resources to the learning platform, and assign learning tasks [21,22]. e teacher should explain the objectives of the learning tasks and let students understand the learning tasks.…”
Section: Preclassmentioning
confidence: 99%
“…Prelearning is the initial stage of constructing the meaning of the knowledge students have learned. Before the lesson, teachers post learning objectives and learning content online, upload multimodal learning resources to the learning platform, and assign learning tasks [21,22]. e teacher should explain the objectives of the learning tasks and let students understand the learning tasks.…”
Section: Preclassmentioning
confidence: 99%
“…The positive perceptions regarding the practices of online learning can be traced among other from the research conducted by [16], [17]. On the positive side, the research results showed that learners had a high level of participation in synchronized online EFL courses in their online learning experiences [16]. The ease and flexibility of online learning were also pointed out in the research [18].…”
Section: Perceptions and Attitudes Towards Online English Learningmentioning
confidence: 81%
“…The results of the empirical research review analysis indicated that the implementation of online learning was perceived positively and negatively by participants during Covid-19 pandemic. The positive perceptions regarding the practices of online learning can be traced among other from the research conducted by [16], [17]. On the positive side, the research results showed that learners had a high level of participation in synchronized online EFL courses in their online learning experiences [16].…”
Section: Perceptions and Attitudes Towards Online English Learningmentioning
confidence: 96%
“…Courtney et al (2022) [5] emphasize the benefits of group note-taking activities in online learning as evidence in favor of this conclusion. Cui and Wang (2021) [6] concur that students should carefully consider the language they use when taking notes and that a blended learning approach is practical. Collectively, these studies suggest that collaborative note-taking can enhance note quality and recall, that a blended learning approach can maximize the learning experiences of EFL learners, there is a significant difference in responses among different age groups ISSN 2663-8169 Vol.…”
Section: Resultsmentioning
confidence: 99%